2020
DOI: 10.1007/s10461-020-02983-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Among People Living with HIV: A Systematic Review

Abstract: This systematic review summarizes the evidence on the earliest patients with COVID-19-HIV co-infection. We searched PubMed, Scopus, Web of Science, Embase, preprint databases, and Google Scholar from December 01, 2019, to June 1, 2020. From an initial 547 publications and 75 reports, 25 studies provided specific information on COVID-19 patients living with HIV. Studies described 252 patients, 80.9% were male, the mean age was 52.7 years, and 98% were on antiretroviral treatment (ART). Co-morbidities in additio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
158
1
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 46 publications
8
158
1
15
Order By: Relevance
“…This work builds on previous reviews on specific sexual health issues and COVID-19, which generally focused on the intersection of HIV and COVID-19 and did not examine sexual health more broadly. [6][7][8] We found that MSM may be moving back toward pre-pandemic levels of sexual activity. Abstinence-based strategies to limit HIV transmission are generally ineffective 133 and it is not reasonable to expect people to refrain from sexual activity amid a pandemic.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This work builds on previous reviews on specific sexual health issues and COVID-19, which generally focused on the intersection of HIV and COVID-19 and did not examine sexual health more broadly. [6][7][8] We found that MSM may be moving back toward pre-pandemic levels of sexual activity. Abstinence-based strategies to limit HIV transmission are generally ineffective 133 and it is not reasonable to expect people to refrain from sexual activity amid a pandemic.…”
Section: Discussionmentioning
confidence: 82%
“…While several reviews have sought to synthesise existing and fast-changing evidence on COVID-19 and health outcomes, little attention has been paid to the pandemic's effects on sexual health and wellbeing. There have been, however, several reviews focused on HIV specifically, [6][7][8] but not on sexual health more broadly. Sexual health is a central feature in overall health and well-being, and in the socioeconomic development of communities and countries 9 ; understanding if and how the COVID- 19 11 Reporting of results conformed to Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Positive outcomes have been reported in case series from Italy [ 34 ], Spain [ 35 ], Germany [ 36 ] and the US [ 37 ]. However, a recent systematic review reported high proportion of death among COVID-19 and HIV co-infected patients [ 38 ] and HIV doubled the risk of COVID-19 mortality in South Africa [ 39 ]. Nigeria has one of the largest numbers of people living with HIV in SSA and there is greater concern for those with low CD4 cell count, advanced disease, high viral load, and those not on antiretroviral treatment (ART) given that COVID-19 also has adverse immunological and clinical effects [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forewarning to take extra deterrents against COVID-19 has been emphasized for persons with comorbidities such as asthma, diabetes, severe cardiovascular conditions, obesity, chronic diseases, and immune-compromised persons, including PLWH [7][8][9][10]. In addition, PLWH have higher rates of certain underlying health conditions [11].…”
Section: Introductionmentioning
confidence: 99%